Pertumbuhan Tanaman Jahe Emprit (Zingiber Officinale Var. Rubrum) pada Media Tanam Pasir dengan Salinitas yang Berbeda - Sari, Hefika Cipta; Darmanti, Sri; Hastuti, Endah Dwi (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2006)
The aim of this research to know influence the salinity to growth of ginger emprit (Zingiber officinale var. Rubrum) and know NaCl concentration can maintain ginger emprit growth. Research use Complete Random Device (RAL) single Pattern. The treatment of NaCl concentration ( PO = 0 % o, P1 = 3 % o, P2 = 6%o, P3 = 9 % o, P4 = 12 % o). Colected data using analysis of variance followed by Duncan’s Multiple Range Test at 5% significance level. The results showed that treatment of different salinity give different influence to growth of ginger emprit. Treatment of concentration salinity 3%o can maintain growth of ginger emprit posed at by wet weight, dry weight and amount of bud . Excelsior salinity cause reduced of growth of ginger emprit.